3x+1x-1=6x+1

Simple and best practice solution for 3x+1x-1=6x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+1x-1=6x+1 equation:


Simplifying
3x + 1x + -1 = 6x + 1

Reorder the terms:
-1 + 3x + 1x = 6x + 1

Combine like terms: 3x + 1x = 4x
-1 + 4x = 6x + 1

Reorder the terms:
-1 + 4x = 1 + 6x

Solving
-1 + 4x = 1 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-1 + 4x + -6x = 1 + 6x + -6x

Combine like terms: 4x + -6x = -2x
-1 + -2x = 1 + 6x + -6x

Combine like terms: 6x + -6x = 0
-1 + -2x = 1 + 0
-1 + -2x = 1

Add '1' to each side of the equation.
-1 + 1 + -2x = 1 + 1

Combine like terms: -1 + 1 = 0
0 + -2x = 1 + 1
-2x = 1 + 1

Combine like terms: 1 + 1 = 2
-2x = 2

Divide each side by '-2'.
x = -1

Simplifying
x = -1

See similar equations:

| -6(-3x+8)=168 | | 56=-2(21-19)+4(19-4) | | m^2-16m+55=0 | | 86=3x+5x-2 | | 6(8y-5)=72 | | 2m+6+5m+10=23 | | solvex^4+9x-7=0forx | | 8=2x-x+1 | | 10x^2+12-16=0 | | 5m-5+2m=2 | | 3x-8(-3-5x)=24 | | 3+x-2x=6 | | m^2=-23m-132 | | x+5(2*4x)-3=14 | | -6+6x+7x=-162 | | 6(2x-4+2x-4)=72 | | m^2=5m+66 | | x^2+25x-500=0 | | 3r+4r-7=41 | | 3x+1+x=-7 | | 48-(-23)= | | 8d-6d+3=8 | | 1.1=x+(1+x) | | 2c+3+4d-c+d= | | 6x^2=55x | | X^2+y^2-7=0 | | 5c+4d-c+d= | | 10+7x=-74 | | e^5x+7=10 | | Y+4+y-6=66 | | 5.7+77=8.2+12 | | 2(2x-1)=22 |

Equations solver categories